IUTAM Symposium on Vibration Control of Nonlinear Mechanisms and Structures Proceedings of the IUTAM Symposium held in Munich, Germany, 18-22 July 2005 - Ulbrich, H.; Günthner, W. (Solid Mechanics and Its Applications,, 2005)
During the last decades, the growth of micro-electronics has reduced the cost of computing power to a level acceptable to industry and has made possible sophisticated control strategies suitable for many applications. Vibration c- trol is applied to all kinds of engineering systems to obtain the desired dynamic behavior, improved accuracy and increased reliability during operation. In this context, one can think of applications related to the control of structures' vib- tion isolation, control of vehicle dynamics, noise control, control of machines and mechanisms and control of ?uid-structure-interaction. One could continue with this list for a long time. Research in the ?eld of vibration control is extremely comprehensive. Pr- lems that are typical for vibration control of nonlinear mechanisms and str- tures arise in the ?elds of modeling systems in such a way that the model is suitable for control design, to choose appropriate actuator and sensor locations and to select the actuators and sensors. Theobjective of the Symposium was to present anddiscuss methodsthat contribute to thesolution of such problems and to demonstrate the state of the art inthe ?eld shown by typical examples. The intention was to evaluate the limits of performance that can beachievedby controlling the dynamics, and to point out gaps in present research and give links for areas offuture research.Mainly, it brought together leading experts from quite different areas presenting theirpoints of view.